Empowering people with disabilities (PWDs) via information communication technology (ICT): the case of Malaysia - Mohamad Diah, Nurazzura; Osman, Osman Mohamed (Zes Rokman Resources, 2017)
Information and communication technology (ICT) skills have become basic requirements to compete in the labour market. However, persons with disabilities (PWDs) face financial, social and environmental difficulties which form barriers to acquiring these skills. Thus, it contributes to the weakening of their competitiveness in the labour market. The main objective of this study is to identify the extent of the contributions of ICT in empowering Malaysian persons with disabilities (PWDs) to compete in the labour market and get jobs. The study used a qualitative approach. Twenty interviews were conducted with Malaysian PWDs who are working in jobs related to ICT and represent institutions in the public and private sectors. The findings reveal that ICT plays a key role in empowering PWDs in employment. However, efforts to empower PWDs in the ICT sector are weak. The study also found that Malaysian PWDs face financial, social and environmental problems in accessing sources of ICT which contributes to the weakening of their competitiveness in the labour market. Serious efforts should be made to develop awareness in Malaysian society about the importance of empowering PWDs via ICT. PWDs are an integral part of the Malaysian society and as such it is the responsibility of the society to enable them to lead a dignified life and contribute effectively to nationbuilding. Indeed, ICT has an essential role in empowering PWDs. It is a major tool in strengthening the skills of the disabled in order to compete in the labour market.